2016
DOI: 10.1002/acr.22996
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Consequences of Multimorbidity in the General Population: There is No Chronic Disease Management Without Rheumatic Disease Management

Abstract: Objective. To identify empirical model-based patterns of multimorbidity from chronic noncommunicable diseases in the general population, with a focus on the contribution of rheumatic and musculoskeletal diseases (RMDs), and to quantify their association with adverse health outcomes. Methods. Cross-sectional data from the Portuguese Fourth National Health Survey were analyzed (n 5 23,754). Latent class analysis was used to identify patterns of coexistence of 11 chronic noncommunicable diseases (RMDs, diabetes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 43 publications
5
42
1
2
Order By: Relevance
“…After selecting the number of latent classes (also referred to as patterns) among those with the lowest Bayesian Information Criterion (BIC), we found that multimorbidity in the Portuguese population could be summarized into four patterns of chronic non-communicable diseases co-occurrence, that were labeled according to disease frequency as "low disease probability" (reference pattern), "cardiometabolic conditions", "respiratory conditions" and "RMDs and depression". We also found that RMDs were highly prevalent across all multimorbidity patterns: 38.6% in "cardiometabolic conditions", 53.5% in "respiratory conditions" and 66.7% in "RMDs and depression", while only 7.8% in "low disease probability" pattern [15].…”
Section: Non-communicable Diseasesmentioning
confidence: 60%
See 3 more Smart Citations
“…After selecting the number of latent classes (also referred to as patterns) among those with the lowest Bayesian Information Criterion (BIC), we found that multimorbidity in the Portuguese population could be summarized into four patterns of chronic non-communicable diseases co-occurrence, that were labeled according to disease frequency as "low disease probability" (reference pattern), "cardiometabolic conditions", "respiratory conditions" and "RMDs and depression". We also found that RMDs were highly prevalent across all multimorbidity patterns: 38.6% in "cardiometabolic conditions", 53.5% in "respiratory conditions" and 66.7% in "RMDs and depression", while only 7.8% in "low disease probability" pattern [15].…”
Section: Non-communicable Diseasesmentioning
confidence: 60%
“…In this context patterns are interpreted as mutually exclusive with regard to the assignment of individuals, but the same disease may (and does) occur in more than one pattern, e.g., even though RMDs were more likely in subjects assigned to the pattern "RMDs and depression" (66.7%), an RMD probability of 38.6% still exists in the "cardiometabolic conditions" pattern. Overall, the population impact of NCDs seems to be comparatively overestimated when considering the traditional GBD-defined groups, since in the latter approach PAF interpretation assumes the complete and irreversible elimination of an NCD or group, while in the empirical approach PAF interpretation considers the change of class membership into the "low disease probability" pattern, which still has some disease probability (including a 7.8% prevalence of RMDs) [15]. Whereas, in our first approach exposure was defined deterministically, since all individuals reported who RMDs were classified as exposed, in our Collected only in one trimester, due to logistic restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Registers allowed the study of comorbidities in real life, whereas in clinical trials patients with major comorbidities are excluded; they elucidated the notion of multimorbidity patterns [33].…”
Section: Registries In Rheumatic Diseasesmentioning
confidence: 99%